"Traveling Codes" Leuphana Workshop – 30-31 March 2017. Issue 1 (October 2017) - Vigni, Fabrizio Li
This note reports on the two-day workshop on environmental sciences, "Traveling Codes", held at Leuphana University in Lüneburg, Germany. The metaphor of Traveling Codes is "to make sense of what happens when climate science travels – whether in the form of mobile scientific tools, models, and software codes, circulating data sets and standards". Participants came from philosophy, sociology, history, and geography, although climate science, hydrology, marine science were the main environmental sciences studied. Historical, policy making, management, and interdisciplinary issues were discussed, but for the next meetings of this network, it would be desirable if the members included other objects of study, such as climatic adaptation measures, the geoengineering debate, and alternative ways of living and producing.